A Combined Radio and Underwater Wireless Optical Communication System based on Buoys. (January 2016) - Song, Yuhang; Tong, Zheng; Cong, Bo; Yu, Xiangyu; Kong, Meiwei; Lin, Aobo
Abstract: We propose a system of combining radio and underwater wireless optical communication based on buoys for real-time image and video transmission between underwater vehicles and the base station on the shore. We analysis how the BER performance is affected by the link distance and the deflection angle of the light source using Monte Carlo simulation.